Challenges to Nutrition Therapy in the Pediatric Critically Ill Obese Patient. (June 2015) - Martinez, Enid E.; Ariagno, Katelyn; Arriola, Aldis; Lara, Kattina; Mehta, Nilesh M.
Background: Obesity has been associated with poor clinical outcomes in critically ill children. The optimal approach to nutrition therapy in this vulnerable cohort is unclear. Methods: We report the nutrition management of 2 obese patients admitted to a pediatric intensive care unit (PICU). We focus on their nutrition assessment, energy requirements, and macronutrient delivery. Results: Case 1 describes a 19-year-old male, body mass index (BMI) 52.4 kg/m 2, who was admitted after emergent orthopedic surgery. Case 2 describes a 13-year-old male, BMI 31.5 kg/m 2, who was admitted with respiratory distress. Average PICU length of stay was 2 months. Nutrition assessments, including weight and height, were obtained early and regularly. Skinfold measurements were challenging. Estimated energy expenditure by predictive equations was significantly higher compared with measured resting energy expenditure (MREE) by indirect calorimetry in both cases. The Mifflin St-Jeor equation (in case 1) overestimated MREE by 681 kcal/d; the Schofield equation (in case 2) overestimated MREE by 662 kcal/d. Both patients had barriers to enteral nutrition and prolonged periods of time when they received no enteral nutrition, requiring parenteral nutrition for 28% and 75% of their PICU stay, respectively. Average daily protein delivered was 0.8 g/kg and 1 g/kg, below adult recommended protein intake for obese patients and pediatric recommendations for age. Conclusions: These cases were notable for (1) challenges to anthropometric assessments, (2) inaccurate estimates of energy requirements, (3) suboptimal enteral nutrition delivery, (4) need for supplemental parenteral nutrition, and (5) suboptimal protein intake. Research is needed to determine the best approach to nutrition therapy in this cohort.